A Orientação Profissional no CEFET-Campos/UNED-Macaé: reflexos das mudanças no mundo do trabalho - Abrunhosa, Maria Luiza de Oliveira (2004)
This work consists of a reflection about the role of discipline Interpersonal Relations in the formation of the pupils of the high school of the CEFET-Campos/UnED-Macaé, searching to contribute for the analysis of the materialization of the recent educational reforms in the scope of the Federal Institutions of Technological Education. Conceiving the concept of that it discipline it the Interpersonal Relations it would be a kind of professional orientation, we look for to argue that the changes in the objectives of this activity would be a requirement of the new professionalization proposal for the current educational legislation. In the development of our inquiries we verify the relationship of the education with the different stages of the development in the way of capitalist production and search to approach the economic and social transformations, occured in the three last decades, to the adoption of the pedagogy of competences abilities as ordenadora of the educative relations. The research looked for to demonstrate that, in sight of the objectives of the educative reforms and the pragmatic character of the pedagogy of competences, the insertion in the course of study of high school of the UnED-Macaé of one discipline as Interpersonal Relations is directed the promotion of the adaptation of the youngs to the instability of the new times.